Cultural Transformation of Kiai Leadership in Madura: From Religious Educators to Political Leaders - Moh Abdullah; Kusaeri Kusaeri (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research examines the transformation of kiai leadership in Madura, shifting from religious roles to political authority. This change reflects broader socio-political dynamics in Indonesia, where religious figures increasingly engage in politics. Madura, with its strong Islamic traditions, provides a vital case study to understand the factors driving this transformation and its impacts on local society and politics. Data was collected through field observations and interviews with nine informants, including three cultural figures, three academics, and three kiai. Key findings reveal that kiai leadership has evolved from a focus on education and social preaching to active involvement in nationalist political dynamics. Kiai now serve not only as spiritual leaders but also as influential political actors. This transformation is driven by socio-political changes in Indonesia, offering greater opportunities for religious figures in the political arena. Consequently, there has been a shift in the leadership structure and function within the Madurese community, with kiai assuming more complex and strategic roles. The significance of these findings lies in their contribution to academic literature and practical applications. For the academic community, this research provides new insights into the dynamics of kiai leadership in Madura, enriching the discourse on the intersection of religion and politics in Indonesia. Practically, understanding the transformation of kiai roles aids policymakers and community leaders in developing strategies to manage the relationship between religious institutions and politics. Additionally, these insights assist kiai and other religious leaders in navigating their evolving roles amidst ongoing socio-political changes.